STUDI TENTANG PERILAKU MEMBOLOS PADA SISWA SMA SWASTA DI KABUPATEN BANYUASIN - Sariyasni, Sariyasni; Budiyono, Budiyono (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Truant behaviour was behavior that should be handled because it can affect the academic, behavior that deviates from the rules of the school and student morale. This fact occurs at SMA Karya Sembawa, SMA PGRI Pulau Harapan and SMA Bina Mandiri. This research aimed to determine the factors underlying the truant students as well as to determine the pattern of truant behavior based on factors encountered. As understood the impact of truant behavior was experienced failure in learning. The method used in this research is descriptive qualitative. The subjects in this research were students of class X (ABC 1 and ABC 2) and XI IPS (ABC 3) at SMA Karya Sembawa, the students of class XI IPS (ABC 4) and XI IPA (ABC 5 and ABC 6) at SMA PGRI Pulau Harapan, and the students of class X (ABC7) and XI IPS (ABC 8 and ABC 9) SMA Bina Mandiri. Data collection techniques in this research in the form of interviews to obtain information about the factors that encourage students to play truant, observations to obtain other information which supports the data that have been obtained and documentation to obtain the data subject's identity and test results MPCL. Sampling technique using purposive sampling technique. While the data analysis technique used was triangulation technique shows that the factors causing the truant behavior problems stemming from the self, family factors, and school factors with truant behavior pattern that was playing playstation or internet, hanging out, hanging out with friends who like play truant the class. Results of this research declare truant behavior can affect academic school, because it can not complete the lesson topic on the same day.